2020
DOI: 10.1002/joc.6738
|View full text |Cite
|
Sign up to set email alerts
|

Moisture flows on Southeast Brazil: Present and future climate

Abstract: The characterization of the moisture flows over South America, with a special focus on the Southeast Brazil (SEB), was performed through the analysis of 21 Earth System Models (ESMs) belonging to the Coupled Model Intercomparison Project Phase 5 (CMIP5) for the present climate (1971-2000) and projections for the late 21st century (2071-2100) using a scenario of high radiative forcing (RCP 8.5). The results show that the ESMs simulate well the spatial distribution of the flow and the divergence of moisture in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…South America is among the regions that can be most impacted, and the projected changes in the mean and extreme regimes of precipitation, temperature, humidity transport (e.g., PBMC, 2014;Torres and Marengo, 2014;Avila-Diaz et al, 2020b;Penna et al, 2021;Torres et al, 2021), among other climate disturbances, can considerably affect agricultural production, water, energy and food security nexus, frequency and intensity of droughts, floods and heat waves, among countless other impacts (Field et al, 2012(Field et al, , 2014IPCC, 2012;Marengo et al, 2014Marengo et al, , 2021Debortoli et al, 2017;Betts et al, 2018;Feron et al, 2019;Lapola et al, 2019Lapola et al, , 2020Mahlknecht et al, 2020). For example, Betts et al (2018), using climate projections compatible with the warming thresholds of the Paris Agreement (1.5 C and 2 C), identified that temperature extremes could get even hotter.…”
Section: Introductionmentioning
confidence: 99%
“…South America is among the regions that can be most impacted, and the projected changes in the mean and extreme regimes of precipitation, temperature, humidity transport (e.g., PBMC, 2014;Torres and Marengo, 2014;Avila-Diaz et al, 2020b;Penna et al, 2021;Torres et al, 2021), among other climate disturbances, can considerably affect agricultural production, water, energy and food security nexus, frequency and intensity of droughts, floods and heat waves, among countless other impacts (Field et al, 2012(Field et al, , 2014IPCC, 2012;Marengo et al, 2014Marengo et al, , 2021Debortoli et al, 2017;Betts et al, 2018;Feron et al, 2019;Lapola et al, 2019Lapola et al, , 2020Mahlknecht et al, 2020). For example, Betts et al (2018), using climate projections compatible with the warming thresholds of the Paris Agreement (1.5 C and 2 C), identified that temperature extremes could get even hotter.…”
Section: Introductionmentioning
confidence: 99%
“…The concurrence of different climate modes of natural variability may explain part of the intensification of drought conditions in recent decades, as suggested by Kayano et al [97]. They may act in synergy blocking the moisture transport from different oceanic regions to the basin, triggering strong drought conditions [99,100]. This statement is confirmed by several studies that found that the extreme drought events during the austral rainy season have been consistent with near surface atmospheric circulation changes and a reduced moisture flow coming from the tropical Atlantic region [10,12,18].…”
Section: Discussionmentioning
confidence: 93%
“…The Amazon moisture recycling system has been examined on its role to maintain some of the global climate processes 6,7 . The equatorial Atlantic Ocean provides moisture to the northern region of South America, promoting precipitation along the Amazon basin 8, 9,10 . A portion of the transported water vapor reaches the western portion of the basin with replenished water vapor content supplied by the Amazon forest evapotranspiration 11 .…”
Section: Introductionmentioning
confidence: 99%